Students' difficulties with respect to the language of mathematics in the mathematics classroom - Ummi Kalsum, Hakim (Universiti Malaysia Sarawak (UNIMAS), 2009)
The aim of this study is to investigate the difficulties faced by the secondary school students in mathematics classroom specifically focusing on the difficulties of the language of mathematics. This study will identify the students' difficulties in learning and understanding the language of mathematics, the causes of the difficulties and suggested strategies to overcome the difficulties. Six students from a secondary school in Kuching district participated in this study. The data that was obtained from a short assessment and interview had been analysed and tabulated. The result revealed that the major difficulties in understanding the language of mathematics is vocabulary of mathematics and the causes is the mathematics itself. The most popular strategy in overcoming the difficulties in understanding the language of mathematics is group discussion. The result of this study also suggested that students should increase their vocabulary of mathematics by playing mathematics puzzles.